EQUIVALENT ELASTIC MODULUS OF THE HONEYCOMB CORE BASED ON FEM MODEL - ZHOU JinCui; SHENG MeiPing; ZHANG AnFu (Jixie qiangdu)
The honeycomb core model was built by finite element method（ FEM）. And based on Hooke ’s law,the equivalent elastic modulus of honeycomb core influenced by the change of cell number was studied. The result indicates that the horizontal equivalent elastic modulus is affected slightly while the vertical equivalent elastic modulus is influenced severely by the changes of cell number in horizontal direction. The changes of cell number in vertical direction have a strong impact on the horizontal equivalent elastic modulus while that affect the vertical equivalent elastic modulus slightly. When the ratio of honeycomb core’s size in horizontal direction to that in vertical direction is less than 1. 3,the horizontal equivalent modulus is less than the vertical equivalent elastic modulus. On the other hand,the horizontal equivalent modulus is greater than or equal to the vertical equivalent elastic modulus. For the large-scale structure,a honeycomb core with similar proportion can be established to calculate the equivalent elastic modulus.